A Preliminary Diction Study of the Philippine Magna Carta of Women: Words as Shapers of Filipinas' Rights - Ruizo, Liway Czarina S. (Review of Women's Studies; Vol 21 No 1 (2011): Review of Women's Studies Volume XXI, Number 1 (January-June 2011))
Proceeding from the theory that Language is the incarnation of a speaking community's valued experience and reality-shaping power, this paper looks into the very language used in the 2009 Philippine Magna Carta for Women, and explores how the wording of this legislative milestone for Filipinas strengthen women's rights, or actually weaken or defeat the purpose thereof. Taking into account overlapping considerations of the law-making process as well as statutory construction, this paper humbly offers the preliminary conclusion that although the law in the main affords security for women's rights, in the fine, it contains provisions and clauses that are not as accurately phrased, so that they open up crevices for repression, oppression, abuse and misuse to seep into the otherwise watertight gender-equality law.